PENGARUH VARIASI PRODUK, ELECTRONIC SERVICE QUALITY DAN WORD OF MOUTH TERHADAP MINAT BELI PADA TOKO JAMU JUICE DALUNG - Luh Putu Petrisia Pradnya Wulandari; I Gusti Ngurah Agung Gede Eka Teja Kusuma; Ni Putu Cempaka Dharmadewi Atmaja (VALUES, 2023)
Purchase intention is something related to the consumer's plan to buy the product or service needed in a certainperiod. Factors that can influence purchase intention include product variety, electronic service quality and wordof mouth. This study aims to determine and analyze the effect of product variation, electronic service quality andword of mouth on buying interest at Jamu Juice Dalung Shop. The research location was at Dewi Deva Devi No.4,Pengilian Hamlet, Dalung Village, Badung Regency, Bali. Jamu Juice Shop, with the object of this research is tomeasure the effect of product variation, electronic service quality, and word of mouth on buying interest at Dalung Jamu Juice Shop. The population in this study were consumers of Jamu Juice Stores whose number is not knownwith certainty, with a total sample of 85 respondents. The data analysis technique used in this study is multiplelinear regression analysis. The results showed that product variation, electronic service quality and word ofmouth have a positive and significant effect on buying interest in Dalung Jamu Juice Shop.